Effects of supplemental irrigation on yield and yield attributes of chickpea (Cicer arietinum L.) in western Ethiopia - Ousman, Yenus; Alemayehu , Getachew; Ayalew, Dereje (Ethiopian Journal of Science and Technology, 2025)
<main class="pkp_structure_main col-xs-12" role="main"> Terminal moisture stress is one of the major factors that reduce the yield of chickpea when it is grown using residual moisture. Field experiment was conducted for two consecutive years (2015/16 and 2016/17) at Teda research site, northwestern Ethiopia to investigate the effect of Supplemental Irrigation (SI) on yield and yield attributes of chickpea (Habru variety). The treatments comprised of six SI levels (no SI/rain-fed, SI at: 50% flowering, 50% pod setting; vegetative + 50% flowering, vegetative + 50% pod setting stages). The treatments were laid out in randomized complete block design with three replications. Data were analyzed using SAS software, and means were separated by least significant difference test. The result showed that the effect of SI on water use efficiency, yield and most yield components of chickpea such as weight of 100-seed, biomass yield, number of secondary branch, pods and seeds plant-1 was significant. SI generally decreased the water use efficiency of chickpea compared to rain-fed condition. Based on two-year result, SI twice at vegetative + pod setting produced maximum seed yield (30.02 q ha-1), which was at par with that of SI twice at vegetative+ flowering (29.30 q ha-1) and once at vegetative stages (29.17 q ha-1). SI once at vegetative, twice at vegetative + flowering and twice at vegetative + pod setting stages increased seed yield by 12, 17 and 19% in 2015; and by 35, 24 and 36 % in 2016, respectively, compared to rain-fed condition. SI once at vegetative stage provided maximum net benefit (45880.40 ETB ha -1), with a marginal rate of return (477%) greater than minimum acceptable level (100%). Moreover, it had the highest water use efficiency among SI treatments. Therefore, SI once at vegetative stage can be recommended as the best management option for chickpea production in the study area. </main>